2002
DOI: 10.1055/s-2002-28518
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of (Alkylthio)chloroacetylenes with Thiosemicarbazones: A Route to Functionalized Thiazoles

Abstract: Alkylthio)chloroacetylenes 1 react with thiosemicarbazones 2 at room temperature in a medium of aliphatic ketone to form hydrochlorides of 2-alkanone-N-[4-(organylthio)-1,3-thiazol-2-yl]hydrazones 3 in yields of up to 65%.Although poorly understood so far, the reactions of (organylthio)chloroacetylenes 1 with S,N-multinucleophiles provide a potential source of new classes of polyfunctional unsaturated compounds, including heteroatomic ones. Moreover, from a fundamental viewpoint, these present an essential sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…As we conclude that the 13 C NMR chemical shifts given in ref are very likely not the ones of 10a , and the chemical shift of the internal standard C 1 70 given in Table might not be correct. However, comparison of the 13 C chemical shifts of similar compounds have indicated that the shift for C 1 is on the order of about 14−15 ppm ( 9a , ref : 14.8 ppm, 12 : 14.5 ppm, Et 2 S, ref : 14.8 ppm). Thus, the authors are confident that the experimental values of the real compound will be within 6 ppm deviation to the theoretical results given here.…”
Section: Resultsmentioning
confidence: 99%
“…As we conclude that the 13 C NMR chemical shifts given in ref are very likely not the ones of 10a , and the chemical shift of the internal standard C 1 70 given in Table might not be correct. However, comparison of the 13 C chemical shifts of similar compounds have indicated that the shift for C 1 is on the order of about 14−15 ppm ( 9a , ref : 14.8 ppm, 12 : 14.5 ppm, Et 2 S, ref : 14.8 ppm). Thus, the authors are confident that the experimental values of the real compound will be within 6 ppm deviation to the theoretical results given here.…”
Section: Resultsmentioning
confidence: 99%
“…In order to obtain new heterocyclic systems with potential photochromic properties and biological activity, we were the first to study the reaction of organylthiochloroacetylenes with dialkyl-substituted thiosemicarbazones, and proved the structure of the resulting products [127,128]. Considering the bidentity of thiosemicarbazones as nucleophiles and the presence of three reaction centers in the haloacetylenes molecule-the halogen atom, terminal (C α ) and internal (C β ) carbon atoms, the result of these reactions were not predictable.…”
Section: Functional Thiazole Derivativesmentioning
confidence: 99%
“…For instance, the reactions with alkylenediamines, 2 2-hydroxyethylamine 3 2-hydroxy-N,Ndimethylamine, 4 thiosemicarbazones, 5 proceed by nucleophilic substitution of the acetylenic chlorine forming ynammonium salts which further undergo cyclization. In this way it was possible to obtain imidazole, oxazolone, oxazolidine, oxazine, and thiazole derivatives which, in certain cases, display effective complex-forming properties or high antimicrobial and antitumor activity.…”
Section: Introductionmentioning
confidence: 99%